Internalisasi Nilai-Nilai Islam Terhadap Bank Syariah - Bachrul Ulum (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2020)
This research report is motivated by the large number of sharia financial institutions that have emerged and the increasing number of sharia banks that provide financial services while meeting the increasingly diverse needs of society. With the current abundance of sharia banking, there are accusations that sharia banking is a conventional bank that only has a sharia label attached to it. However, nowadays sharia banks always try to implement Islamic values based on Sharia principles. Sharia banking has a big influence on people's economic activities. Various sharia banking products are expected to be able to encourage and accelerate people's economic progress in accordance with Islamic principles. In Islamic principles, economic activity cannot be separated from the postulate of faith in Allah SWT and even becomes a built in control for economic actors. From here, sharia banking was built and designed to improve the standard of human life. Sharia banking is expected to become an alternative and even a decisive solution for the development of the national economy, especially for Muslims.